Warranty claim analysis considering human factors - Wu, Shaomin (Elsevier, 2011)
Warranty claims are not always due to product failures. They can also be caused by two types of human factors. On the one hand, consumers might claim warranty due to misuse and/or failures caused by other human factors. Such claims might account for more than 10% of all reported claims; on the other hand, consumers might not be bothered to claim warranty for failed items that are still under warranty, or claim warranty after they have experienced several intermittent failures. These two types of human factors can affect warranty claim costs. However, research in this area has received rather little attention. In this paper, we propose three models to estimate the expected warranty cost when the two types of human factors are included. We consider two types of failures, intermittent and fatal failures, which might result in different claim patterns. Consumers might report claims after a fatal failure has occurred, and upon intermittent failures they might report claims after a number of failures have occurred. Numerical examples are given to validate the results derived.
Keywords: warranty claim; non-failed but reported; failed but not reported; human factor; intermittent failure; fatal failure